The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.macromol.0c00146
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Depolymerization of Nanowires Self-Assembled from Micelles

Abstract: Supramolecular polymerization has been a fascinating frontier of supramolecular chemistry in fabricating well-defined hierarchical nanostructures. However, the reverse process, that is, supramolecular depolymerization in which superstructures disassemble into subunits, is far less explored. In particular, the mechanism and kinetics of supramolecular depolymerization have not yet been reported. In this work, we discovered a thermal-induced supramolecular depolymerization of nanowires formed by supramolecular st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…This disassembly is rather unusual, as MCMs tend to undergo morphological transitions from smaller to larger aggregates (e.g., spherical micelles to worms) or they separate into patchy micelles. [ 42,44,48 ] The herein described process shows that also hydrophobic core domains are able to disassemble into individual chains in water (given low T g and large enough corona), which might be useful for delivering hydrophobic drugs that are released not with chemical triggers, but by mechanical stress.…”
Section: Figurementioning
confidence: 98%
“…This disassembly is rather unusual, as MCMs tend to undergo morphological transitions from smaller to larger aggregates (e.g., spherical micelles to worms) or they separate into patchy micelles. [ 42,44,48 ] The herein described process shows that also hydrophobic core domains are able to disassemble into individual chains in water (given low T g and large enough corona), which might be useful for delivering hydrophobic drugs that are released not with chemical triggers, but by mechanical stress.…”
Section: Figurementioning
confidence: 98%
“…In supramolecular polymerization, the lability of the non-covalent interactions makes the structures intrinsically dynamic and sensitive to changes in molecular functionalities and external conditions. Therefore, aside from increase in temperature, [10][11][12][13] addition of cosolvent, 14,15 and use of supramolecular additives, [16][17][18][19] the modication of structural units by covalent reactions would provide an alternative method to control supramolecular polymerization. Elegant examples have been presented in which adaptation, regulation and replication can be demonstrated by integrating chemical reactions with polymerization processes.…”
Section: Introductionmentioning
confidence: 99%
“…44 Cai and co-workers have well-demonstrated that one-dimensional nanowires readily formed via the fusion of spindle-like micelles along the long axis of the micelles. 45,46 We envision that it might also undergo a directional fusion of ellipsoidal morphologies during the formation of cylindrical nanostructures via PISA of BCPs containing a LC block. However, to the best of our knowledge, the directional fusion effect on the formation of cylindrical nanostructures has been rarely discussed in PISA.…”
Section: Introductionmentioning
confidence: 99%